The core role of macrophages in hepatocellular carcinoma: the definition of molecular subtypes and the prognostic risk system - Wang, Qiaona; Lin, Yunshou; Yu, Wenguan; Chen, Xiaogang; He, Qingqing; Ye, Zhiyu (Frontiers in Pharmacology, 2023)
Background In patients with hepatocellular carcinoma (HCC), tumor microenvironment (TME) is resistant to immunotherapy because of its specificity. It is meaningful to explore the role of macrophage, which is one of the most abundant immune cells in TME, in cellular communication and its effect on the prognosis and immunotherapy of HCC. Methods Dimensionality reduction and clustering of the single-cell RNA-seq data from GSE149614 dataset to identify the cellular composition of HCC. CellChat was used to analyze the communication between different cells. The specifically highly expressed genes of macrophage were extracted for univariate Cox regression analysis to obtain prognostic genes for HCC cluster analysis, and the risk system of macrophage specifically highly expressed genes was developed by random forest analysis and multivariate Cox regression analysis. Prognosis, TME infiltration, potential responses to immunotherapy and antineoplastic drugs were compared among molecular subtypes and between risk groups. Results We found that HCC included 9 identifiable cell types, macrophage had the highest communication intensity with each of the other 8 cell types. 56 of the 179 specifically highly expressed genes of macrophage were significantly correlated with the prognosis of HCC, which classified HCC into three subtypes, which were reproducible and produced different survival outcomes, TME infiltration and immunotherapy responses among the subtypes. The integration of four macrophage specifically highly expressed genes for the development of a risk system, risk score was significantly involved in higher immune cell infiltration, poor prognosis, immunotherapy response rate and sensitivity of six drugs. Conclusions In this study, through single-cell RNA-seq data, we identified 9 cell types, among which, macrophage had the highest communication intensity with the rest cell types. Basing on specifically highly expressed genes of macrophage, we successfully divided HCC patients into three cluster with distinct prognosis, TME and therapeutic response. Additionally, a risk system was constructed, which provided a potential reference index for the prognostic target and preclinical individualized treatment of HCC.